The Effect Of Leadership Style And Work Discipline On Employee Performance At Pt Federal International Finance Central Pamulang - Oktasari, Tyas; Qurbani, Derita; Syatoto, Iman (Pasundan Social Science Development, 2025)
This study aims to determine the influence of leadership style and work discipline on employee performance at PT Federal International Finance Central Pamulang. The research method used is quantitative with data collection techniques through questionnaires distributed to 78 respondents. Data analysis was performed using simple and multiple linear regression with the help of SPSS version 26. The results showed that leadership style has a significant effect on employee performance, with a determination coefficient of 73.0% and the regression equationY = 7.038 + 0.870X1. The t-test results show a t-count of 14.352 > 1.992and a p-value of 0.000 < 0.050. Work discipline also has a significant effect on employee performance, with a determination coefficient of 92.2% and the regression equation Y = 2.336 + 0.923X2. The t-test results show a t-count of 29.936 > 1.992 and a p-value of 0.000 < 0.050. Simultaneously, leadership style and work discipline have a significant effect on employee performance, with a determination coefficient of 92.3% and the regression equation Y = 2.094 + 0.074X1 + 0.862X2. The F-test results show an F-count of 450.116 > 3.12 and a p-value of 0.000 < 0.050. Based on these results, it can be concluded that leadership style and work discipline greatly contribute to improving employee performance at PT Federal International Finance Central Pamulang. Therefore, the company is advised to continuously enhance leadership effectiveness and enforce work discipline to achieve optimal performance